2021
DOI: 10.3390/cells10010126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microbial Short-Chain Fatty Acids on CYP3A4-Mediated Metabolic Activation of Human Pluripotent Stem Cell-Derived Liver Organoids

Abstract: The early and accurate prediction of the hepatotoxicity of new drug targets during nonclinical drug development is important to avoid postmarketing drug withdrawals and late-stage failures. We previously established long-term expandable and functional human-induced pluripotent stem cell (iPSC)-derived liver organoids as an alternative source for primary human hepatocytes. However, PSC-derived organoids are known to present immature fetal characteristics. Here, we treated these liver organoids with microbial sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…For example, butyrate has a detoxification effect on a genipin-induced liver injury by promoting colonic integrity and promoting Nrf2 activation (Luo et al, 2021 ). A study by Mun et al ( 2021 ) showed that an SCFA mixture treatment improved metabolic activation of liver organoids and contributed to the accurate evaluation of the CYP3A4-dependent drug toxicity. In our metabolomics results, the level of pentanoic acid in urine was decreased after GSrE-induced hepatotoxicity, and the level on day 21 was lower than that on day 10.…”
Section: Discussionmentioning
confidence: 99%
“…For example, butyrate has a detoxification effect on a genipin-induced liver injury by promoting colonic integrity and promoting Nrf2 activation (Luo et al, 2021 ). A study by Mun et al ( 2021 ) showed that an SCFA mixture treatment improved metabolic activation of liver organoids and contributed to the accurate evaluation of the CYP3A4-dependent drug toxicity. In our metabolomics results, the level of pentanoic acid in urine was decreased after GSrE-induced hepatotoxicity, and the level on day 21 was lower than that on day 10.…”
Section: Discussionmentioning
confidence: 99%
“…The authors embedded foregut globules in a stromal gel, followed by co-culture with retinoic acid (RA) to directionally differentiate PSCs into foregut-derived organoids, thereby generating more complete organoids containing both epithelial components and mesenchymal cells which can differentiate into supporting lineages. Recently, in response to the disadvantage that PSC-derived organoids exhibit only immature fetal characteristics, Mun et al (2021) used microbial short-chain fatty acids (SCFAs) to simulate changes in the microenvironment of the liver during postnatal development. This approach could increase albumin secretion and P450 activity, as well as the expression of hepatocyte genes ( Aloia et al, 2019 ), which improved the metabolic ripening of IPSC-derived liver organoids.…”
Section: Classification Of Liver Organoidsmentioning
confidence: 99%
“…Hepatocytes in pericentral zone 3 express high levels of CYP enzymes and execute xenobiotic metabolism. Artificial hepatic zonation via a Wnt gradient represents zone 3-specific APAP toxicity that forms toxic reactive metabolites through CYP2E1, CYP1A2, and CYP3A4 [5,[37][38][39][40]. Furthermore, inter-organ interactions can be simulated using this bioengineering technology, which mirrors absorption (gut), distribution, metabolism (liver), and excretion (kidney) [34].…”
Section: Cholestasismentioning
confidence: 99%